Fagopyrum dibotrys extract alleviates hepatic steatosis and insulin resistance, and alters autophagy and gut microbiota diversity in mouse models of high-fat diet-induced non-alcoholic fatty liver disease - Zhang, Dan; Xu, Yongfang; Chen, Hang; Wang, Da; Geng, Zuotao; Chen, Yuanli; Chen, Yan; Xiong, Di; Yang, Rongna; Liu, Xiaoting; Zhang, Yuke; Xiang, Ping; et al. (Frontiers in Nutrition, 2022)
Nonalcoholic fatty liver disease (NAFLD) is a major global health concern with increasing prevalence, with a lack of currently available effective treatment options; thus, the investigation of novel therapeutic approaches is necessary. The study aimed to investigate the outcomes and mechanisms of action of Fagopyrum dibotrys extract (FDE) in a high-fat diet (HFD)-induced mouse model of obesity. The findings showed that FDE supplementation attenuated glucose tolerance, insulin resistance, hepatic steatosis, and abnormal lipid metabolism. In addition, FDE also promoted autophagic activity and inhibited the phosphorylation of TFEB in HFD-fed mice. Furthermore, gut microbiota characterization via 16S rRNA sequencing revealed that the supplementation of FDE increased Bacteroidetes and Verrucomicrobia populations while decreased Firmicutes, thus modifying the gut microbiome. FDE also increased the relative abundance of Akkermansia. Our findings suggest that FDE may protect against HFD-induced NAFLD by activating autophagy and alleviating dysbiosis in the gut microbiome. FDE may be beneficial as a nutraceutical treatment for NAFLD.